R0 Estimation for the African Swine Fever Epidemics in Wild Boar of Czech Republic and Belgium - Marcon, Andrea; Linden, Annik; Satran, Petr; Gervasi, Vincenzo; Licoppe, Alain; Guberti, Vittorio (Veterinary sciences, 2019)
African swine fever (ASF) is a contagious haemorrhagic fever that affects both domesticated and wild pigs. Since ASF reached Europe wild boar populations have been a reservoir for the virus. Collecting reliable data on infected individuals in wild populations is challenging, and this makes it difficult to deploy an effective eradication strategy. However, for diseases with high lethality rate, infected carcasses can be used as a proxy for the number of infected individuals at a certain time. Then R0 parameter can be used to estimate the time distribution of the number of newly infected individuals for the outbreak. We estimated R0 for two ASF outbreaks in wild boar, in Czech Republic and Belgium, using the exponential growth method. This allowed us to estimate both R0 and the doubling time (Td) for those infections. The results are R0 = 1.95, Td = 4.39 for Czech Republic and R0 = 1.65, Td = 6.43 for Belgium. We suggest that, if estimated as early as possible, R0 and Td can provide an expected course for the infection against which to compare the actual data collected in the field. This would help to assess if passive surveillance is properly implemented and hence to verify the efficacy of the applied control measures.
Keywords: African swine fever; R0; wild boar; eradication strategies; Europe; doubling time